CRYPTOCURRENCY CONCEPTS, TECHNOLOGY, AND APPLICATIONS. - Liebowitz, Jay. ([S.l.] : AUERBACH PUBLICATIONS, 2023)
Whether the source is more industry-based or academic research, there certainly appears to be a growing interest in the field of cryptocurrency. The New York Times had a cover story on March 24, 2022, titled "Time to Enter the Crypto Zone?," and they talked about institutional investors pouring billions into digital tokens, salaries being taken in Bitcoins, and even Bitcoin ATMs in grocery stores. Certainly, there have been ups and downs in crypto, but it has a kind of alluring presence that tempts one to include crypto as part of one's portfolio. Those who are "prime crypto-curious" investors are usually familiar with the tech/pop culture and feel they want to diversify a bit in this fast-moving market. Even universities are beginning to offer more courses and create "Centers on Cryptocurrency." Some universities are even requiring their students who take a crypto course to pay the course tuition via cryptocurrency. In response to the growing interest and fascination about the crypto industry and cryptocurrency in general, Cryptocurrency Concepts, Technology, and Applications brings together many leading worldwide contributors to discuss a broad range of issues associated with cryptocurrency. The book covers a wide array of crypto-related topics, including: Blockchain NFTs Data analytics and AI Crypto crime Crypto industry and regulation Crypto and public choice Consumer confidence Bitcoin and other cryptocurrencies. Presenting various viewpoints on where the crypto industry is heading, this timely book points out both the advantages and limitations of this emerging field. It is an easy-to-read, yet comprehensive, overview of cryptocurrency in the U.S. and international markets.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Cryptocurrencies; BUSINESS & ECONOMICS / Banks & Banking